ORGANIZATIONAL CULTURE AND ITS IMPACT ON EDUCATIONAL INSTITUTIONS - Maulida, Maulida Tri Puspita; Hayati, Fitri (Indikator Pendidikan Indonesia, 2023)
Organizational culture are values or norms, or attitudes that can be used as a guide for members of the organization to be able to behave and behave in the organization. And organizational culture also provides a positive influence to improve the performance of its members. School is one of the educational institutions that is given the task and authority to realize national education goals and must carry out its role properly. In carrying out the role of education as an educational institution, schools must be managed properly in order to realize educational goals that have been well formulated and planned. The impact of organizational culture on educational institutions is that the positive impacts that most often occur are the organization acts as a guide so that the goals of achievement can be successful. Organization as an area or place of knowledge. Not only the positive impact, but organizational culture also has a negative impact that can affect the implementation of an organization's goals, while the impact is being in an organization can affect study time, organizing also definitely costs money.